Sistema de informação em AIDS: limites e possibilidades System of information in AIDS: limits and possibilities - Lúcia Yasuko Izumi Nichiata; Hisako Shima (SciELO, 1999)
O artigo faz uma análise do atual Sistema de Informação (SI) em AIDS, apontando as dificuldades com que se defrontou ao buscar caracterizar o modo como ocorria e evoluía em 1995 a epidemia da AIDS na Administração Regional de Saúde de Pirituba-Perus (ARS-8) do município de São Paulo. São enumeradas algumas críticas que a Vigilância Epidemiológica e o SI vêm sofrendo nos últimos anos, tais como a centralização e a desagregação das informações; dados que contemplam aspectos eminentemente biológico e a utilização de formulários complexos. Estas questões somadas às dificuldades que se impuseram ao se buscar caracterizar a epidemia na região, revelou que o sistema, tal como se encontrava estruturado, dificultava a caracterização da epidemia e o acompanhamento sistemático pelos níveis locais de saúde. Chama-se a atenção para a necessidade de revisão da finalidade do SI em AIDS, da natureza e da qualidade dos dados coletados. Reitera-se a importância da integração dos diversos bancos de dados sócio-demográficos e do enfoque microlocalizado do Sl para o Distrito de Saúde. The article makes an analysis of the current System of Information (SI) in AIDS, aiming the difficulties with that was confronted when looking for to characterize the way as it happened and it developed in 1995 the epidemic of the AIDS in the Regional Administration of Health of Pirituba-Perus (ARS-8) of the municipal district of São Paulo. Some are enumerated critics that the Epidemic ,surveillance and the SI they come suffering in the last years, such as the centralization and the disaggregation of the information; the data that contemplate aspects eminently biological, the use of complex forms. These subjects, added to the difficulties that were imposed to the e/she/it to look for to characterize the epidemic in the area, he/she revealed that the system, just as her found structured, it hindered the characterization of the epidemic and the systematic accompaniment for the local levels of health. He/she gets himself the attention for the need of revision of the purpose of the SI in AIDS, of the nature and of the quality of the collected data. It is reiterated the importance of the integration of the several databases partner-demografics of the focus microlocalizado of Sl for the District of Health.